2018
DOI: 10.1210/js.2018-00225
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human FSH Treatment Outcomes in Five Boys With Severe Congenital Hypogonadotropic Hypogonadism

Abstract: ContextRecombinant human FSH (r-hFSH), given to prepubertal boys with hypogonadotropic hypogonadism (HH), may induce Sertoli cell proliferation and thereby increase sperm-producing capacity later in life.ObjectiveTo evaluate the effects of r-hFSH, human chorionic gonadotropin (hCG), and testosterone (T) in such patients.Design and SettingRetrospective review in three tertiary centers in Finland between 2006 and 2016.PatientsFive boys: ANOS1 mutation in two, homozygous PROKR2 mutation in one, FGFR1 mutation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…These findings are in agreement with earlier reports showing a strong suppressing effect of T on AMH (Young et al, 1999;Young et al, 2003;Young et al, 2005). It is important to note that, in boys (Kohva et al, 2018) and men (Young et al, 2005) with gonadotrophin deficiency, recombinant FSH increases AMH, whereas in healthy boys, this effect appears to be overcome by the pubertal increase in intratesticular T levels (Rey, 1998;Grinspon et al, 2013). Indeed, the expression of androgen receptors in Sertoli cells increases significantly at the age of 4 to 8 years (Chemes et al, 2008), and the pubertal decrease in AMH has been shown to be an early, androgen-dependent event (Hero et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with earlier reports showing a strong suppressing effect of T on AMH (Young et al, 1999;Young et al, 2003;Young et al, 2005). It is important to note that, in boys (Kohva et al, 2018) and men (Young et al, 2005) with gonadotrophin deficiency, recombinant FSH increases AMH, whereas in healthy boys, this effect appears to be overcome by the pubertal increase in intratesticular T levels (Rey, 1998;Grinspon et al, 2013). Indeed, the expression of androgen receptors in Sertoli cells increases significantly at the age of 4 to 8 years (Chemes et al, 2008), and the pubertal decrease in AMH has been shown to be an early, androgen-dependent event (Hero et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, some studies investigated the role of replacement of deficient mini-pubertal hormones by using GnRH, or gonadotropins during infancy in patients with CHH to improve reproductive health, especially fertility, later in life (237). However, only some of these studies included cryptorchid boys, and testicular descent was not the primary outcome of most of these studies, making it difficult to assess the effect of this approach on testicular descent (41, 133,[239][240][241][242][243]. As far as we know, only two small studies in France and Greece have investigated the effects of gonadotropin administration during infancy in boys with CHH associated with cryptorchidism, and aimed at induction of testicular descent, or had testicular descent as one of the primary outcome (244,245).…”
Section: Hormonal Treatment In Patients With Congenital Hypogonadotromentioning
confidence: 99%
“…One of the patients (C8) was diagnosed with CHH as a part of CPHD at the age of one month due to low gonadotropin and testosterone levels. The remaining seven boys had no hormonal measurements in infancy available, but they presented other signs of absent minipuberty: six had bilateral cryptorchidism and/or micropenis, and one was diagnosed with biallelic loss-of-function GNRHR mutation (C2) with completely absent LH response in a GnRH stimulation test (Kohva et al 2018). We have earlier described induction of puberty with gonadotropin treatment in five of these boys (patients C1 to C5) (Kohva et al , 2018) and the pubertal status of two of the boys (patients C6 and C7) (Varimo et al , 2017).…”
Section: Methodsmentioning
confidence: 99%
“…We have earlier described induction of puberty with gonadotropin treatment in five of these boys (patients C1 to C5) (Kohva et al , 2018) and the pubertal status of two of the boys (patients C6 and C7) (Varimo et al , 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation